Sub-Tissue Localization of Phytochemicals in Cinnamomum camphora (L.) J. Presl. Growing in Northern Italy - Martina Bottoni; Fabrizia Milani; Marta Mozzo; Daniele Armando Radice Kolloffel; Alessio Papini; Filippo Fratini; Filippo Maggi; Laura Santagostini (Plants, 2021)
In the present paper, we focused our attention on Cinnamomum camphora (L.) J. Presl. (Lauraceae), studied at three levels: (i) micromorphological, with the analysis of the secretory structures and a novel in-depth histochemical characterization of the secreted compounds; (ii) phytochemical, with the characterization of the essential oils from young stems, fruits, and leaves, subjected to different conservation procedures (fresh, dried, stored at −20 °C, stored at −80 °C) and collected in two different years; (iii) bioactive, consisting of a study of the potential antibacterial activity of the essential oils. The micromorphological investigation proved the presence of secretory cells characterized by a multi-layered wall in the young stems and leaves. They resulted in two different types: mucilage cells producing muco-polysaccharides and oil cells with an exclusive terpene production. The phytochemical investigations showed a predominance of monoterpenes over sesquiterpene derivatives; among them, the main components retrieved in all samples were 1,8-cineole followed by α-terpineol and sabinene. Conservation procedures seem to only influence the amounts of specific components, i.e., 1,8-cineole and α-terpineol, while analyses on each plant part revealed the presence of some peculiar secondary constituents for each of them. Finally, the evaluation of the antibacterial activity of the essential oil showed a promising activity against various microorganisms, as Listeria monocytogenes, Staphylococcus aureus, Enterococcus faecalis and Pseudomonas aeruginosa. In conclusion, we combined a micromorphological and phytochemical approach of the study on different plant parts of C. camphora, linking the occurrence of secretory cells to the production of essential oils. We compared, for the first time, the composition of essential oils derived from different plant matrices conserved with different procedures, allowing us to highlight a relation between the conservation technique and the main components of the profiles. Moreover, the preliminary antibacterial studies evidenced the potential activity of the essential oils against various microorganisms potentially dangerous for plants and humans.